The Legacy of Nehru : Appraisal and Analysis - Lobo, Lancy; Shah, Jayesh (Brill | Manohar Publishers & Distributors, 2018)
Even after 127 years, Jawaharlal Nehru remains a beacon for India. He was a titan who provided the architecture of contemporary India. The credit for much of India's progress in myriad fields goes to him. This volume, however, is not a eulogy to that great visionary. It provides rather a critical examination of his legacy in various fields, such as his promotion of India as the Union of federating states, building up of the structure of democratic institutions, enunciation of viable foreign policy, laying the path of economic development on the foundations of equality and cultivating secular ethos. The primary objective of the book is to assess the imprint that Nehru has left behind, and the impact that his thoughts and actions produced on the people of the present and succeeding generations. The volume deliberates on the question whether Nehru had a well-defined economic ideology or foreign policy which could be given a recognized label. It also focuses on how Nehru handled the various sectors and institutions of society. While this volume praises Nehru for providing a durable basis for India's democratic institutions and for endowing them with much legitimacy, it also evaluates many of his negative legacies, such as license raj, the border problems with China and Pakistan, divisive domestic electoral politics, politicization of minorities as vote banks, the Kashmir problem, and corruption in public life.